Anxiety Management at the Time of COVID-19: the Contribution of Physical Activity in Childhood - Manuela Valentini; Gloria Giardina (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction:  Physical activity as an intervention to prevent or mitigate the symptoms of anxiety in childhood is a topic that has not yet found the right valorization in the socio-cultural context, even if it is commonly recognized its importance on health, less common is that it has on psychological well-being, especially of children and adolescents. Research Aim: The article takes into consideration an in-depth Bibliographic Research on the most important search engines, selected on this topic including articles from 2016 to 2021. Evidence-based Facts: Protocols with which we want to demonstrate the positive correlation between anxiety, depression and physical activity and its importance especially in this period of pandemic, which has determined a significant decrease in the levels of physical exercise, significantly increasing the risk of young people to incur in disorders of anxious type and to develop psychological distress. Summary: Prevent and fight with simple but necessary motor solutions, indispensable for this target audience.